Community Perception of Gold Mining Affecting the Water Quality of the Wariori River - Alif Irfan; Hendri Pranata Perangin-Angin; Gandi Y.S Purba (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study examines community perceptions of gold mining and its impact on the water quality of the Wariori River in Aurmios Village. The population involved all residents of Aurmios Village with a sample size of 20 (twenty) people. Using a qualitative research approach based on postpositivism and interpretive philosophy, data were collected through triangulation, combining observation, questionnaires, and interviews. The results show significant negative impacts of illegal gold mining on water quality and community life. The majority of respondents (95%) reported an increase in river water turbidity after mining activities, in line with the findings of Yulianti et al. (2016) and Putri Ade Rahma Yulis (2018) on the increase in Total Suspended Solids (TSS) and heavy metal pollution. In addition, 100% of respondents reported reduced clean water sources, leading to economic and health challenges, such as increased healthcare costs and a shift in livelihoods from fisheries and agriculture to gold mining. Environmental impacts include ecosystem degradation and increased flood risk, and 100% of respondents recognized these issues. In order to address these adverse impacts, the study recommends strict government measures to regulate illegal mining, establish safe and legal mining operations, provide clean water infrastructure, as well as educate communities on the dangers of illegal gold mining. These measures are essential to restore the water quality of the Wariori River and ensure the sustainable well-being of Aurmios villagers. Further research is needed to monitor long-term impacts and develop effective mitigation strategies.